Activism in Bosnia-Herzegovina: Struggles against Dual Hegemony and the Emergence of "Local First". Issue 1 (February 2019) - Puljek-Shank, Randall; Fritsch, Felix
The 2014 protests and plenums in Bosnia-Herzegovina were widely noted for their insertion of economic and social justice topics into the stale public discourse of ethnocracy. They also signified a potential to break with an anemic civil society shaped by international intervention, technocratic "project logic" and apolitical service provision. This article argues for treating these struggles in reference to the dual nature of the hegemony created by both local ethnonationalists and international liberal intervenors. It applies a Gramscian perspective to the processes by which hegemony is created and (re)produced via consensus in civil society. The challenge to dual hegemony can be seen in the central focus of contestation on social justice in economic arrangements as well as in the alternative logics of engagement and organizational forms in society. We describe the tensions arising from this dual challenge in terms of the degree to which they contest or reproduce the predominant anti-politics, a stance of distancing from dialogue or even contact with political actors and institutions. We conclude that the events during and since 2014 have strengthened the means to build an alternative third bloc via a "local first" approach, containing heterogeneous forms of local-scale action with explicitly political strategies.